Победитель забирает все: [роман] / Владимир Колычев - Колычев Владимир Григорьевич (Мент правосудия, 2006)
Экземпляры: ф.23 (20201111) / Инвентарный номер: 60461 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 61 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44